2015
DOI: 10.3390/en8031745
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Storage Off-Gas Emissions from Woody, Herbaceous, and Torrefied Biomass

Abstract: Wood chips, torrefied wood chips, ground switchgrass, and wood pellets were tested for off-gas emissions during storage. Storage canisters with gas-collection ports were used to conduct experiments at room temperature of 20 °C and in a laboratory oven set at 40 °C . Commercially-produced wood pellets yielded the highest carbon monoxide (CO) emissions at both 20 and 40 °C (1600 and 13,000 ppmv), whereas torrefied wood chips emitted the lowest of about <200 and <2000 ppmv. Carbon dioxide (CO2) emissions from woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…According to Ray et al [10], the use of blended and densified feedstocks in conversion pathways instead of conventionally ground biomass from a single source addresses several challenges in the current biomass supply chain, such as transportation, storage, cost, quality, and supply variability. Edmunds et al [11], Sahoo and Mani [50], and Tumuluru et al [51] reported that herbaceous biomass, such as switchgrass, has a bulk density in the range of 150-160 kg/m 3 . Based on the present study, pelleting blends of switchgrass + 2-inch top pine residue increased bulk density values to about 540-580 kg/m 3 .…”
Section: Discussionmentioning
confidence: 99%
“…According to Ray et al [10], the use of blended and densified feedstocks in conversion pathways instead of conventionally ground biomass from a single source addresses several challenges in the current biomass supply chain, such as transportation, storage, cost, quality, and supply variability. Edmunds et al [11], Sahoo and Mani [50], and Tumuluru et al [51] reported that herbaceous biomass, such as switchgrass, has a bulk density in the range of 150-160 kg/m 3 . Based on the present study, pelleting blends of switchgrass + 2-inch top pine residue increased bulk density values to about 540-580 kg/m 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Variable moisture content, low bulk density, and irregular size and shape create feeding, handling, and transportation issues that limit the biomass application at commercial scale for biofuels and biopower generation. Typically, herbaceous biomass after harvesting has a bulk density of 112 to 160 kg/m 3 (Atchison and Hettenhaus, 2004), whereas woody biomass has a bulk density of 220 to 265 kg/m 3 (Tumuluru et al, 2015a). Tumuluru et al (2016) indicated that densification helps to convert the raw biomass resources into an aerobically stable, high-density, tradable, and aggregatable commodity-like product.…”
Section: Introductionmentioning
confidence: 99%
“…This energy can be used for very different purposes, including the production of heat by burning. Of course, when burning biomass, carbon dioxide and other pollutants are released, but it is a gas that has been absorbed into the primary growth of combusted biomass and that will be absorbed during the photosynthesis processes carried out by new plants [3][4][5]. Surely, the assumption that the total emission is zero would be a mistake, because the cultivation of plants used for biomass requires some energy expenditure.…”
Section: Introductionmentioning
confidence: 99%